2013
DOI: 10.1080/ac.68.3.2983420
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization costs of TAVI in one Belgian university hospital

Abstract: In general the analyses showed that only limited options remain for cost reduction of the TAVI hospitalization cost. The most promising option is the reduction of the valve price. Avoidance of complications is hard to achieve given the current state of the art although this would significantly reduce overall costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The transcatheter heart valve (THV) prosthesis itself has a substantial acquisition cost that is 5–6 times that of a surgical prosthesis. The bulk of the previous work on TAVI17 18 20 33 and SAVR34 related costs has focused on the importance of complications and the incremental costs associated with them.…”
Section: Discussionmentioning
confidence: 99%
“…The transcatheter heart valve (THV) prosthesis itself has a substantial acquisition cost that is 5–6 times that of a surgical prosthesis. The bulk of the previous work on TAVI17 18 20 33 and SAVR34 related costs has focused on the importance of complications and the incremental costs associated with them.…”
Section: Discussionmentioning
confidence: 99%
“…A study from the University of Antwerp, Belgium for instance reported average costs of hospitalization of €38,739 [13]. In another study based on the FRANCE registry [27] the estimated average cost of hospitalization was €35,164 [15].…”
Section: Ta Instead Of Tf-tavimentioning
confidence: 98%
“…A Belgian group found costs to be highly insensitive to pre-existing patient characteristics with an average estimate of €38,739 [13]. Similarly Italian and French analyses of TAVR costs reported mean values of €35,841 and €35,164 [14,15].…”
Section: Introductionmentioning
confidence: 97%